Effect of three silver diamine fluoride application protocols on the microtensile bond strength of resin-modified glass ionomer cement to carious dentin in primary teeth - Savil Ramachandra Uchil; Baranya Shrikrishna Suprabha; Ethel Suman; Ramya Shenoy; Srikant Natarajan; Arathi Rao (Wolters Kluwer Medknow Publications, 2020)
Background: Use of silver diamine fluoride (SDF) after selective caries excavation can arrest the further progress of the carious lesion. Application of potassium iodide (KI) can reduce the staining due to SDF.Aim:The aim of the study was to evaluate the effect of the application of SDF, with and without acid etching and KI on the bond strength of resin-modified glass ionomer cement (RMGIC) to the carious dentin of primary teeth. Materials and Methods:In thisin vitro study, caries was induced on the occlusal surface by inoculating Streptococcus mutans strain in 36 extracted primary molars. The teeth were divided into four groups (n = 9), and the following treatments were done to the carious dentin prior to final restoration with RMGIC: Group I: 10% polyacrylic acid conditioner, Group II: 38% SDF, Group III: 37% phosphoric acid etchant followed by 38% SDF, and Group IV: 37% phosphoric acid etchant followed by 38% SDF and 10% potassium iodide solution. The microtensile bond strength was measured using universal testing machine. Failure modes were recorded using a scanning electron microscope. Results: There was no significant difference in microtensile bond strengths between the groups (P = 0.665), with the highest value seen in Group III. Conclusions: Application of SDF with or without acid etching and KI does not affect the bond strength of RMGIC to carious dentin of primary teeth.